Influence of Gestational Age, Secretor, and Lewis Blood Group Status on the Oligosaccharide Content of Human Milk. Issue 5 (May 2017) - Kunz, Clemens; Meyer, Christina; Collado, Maria Carmen; Geiger, Lena; García-Mantrana, Izaskun; Bertua-Ríos, Bibiana; Martínez-Costa, Cecilia; Borsch, Christian; Rudloff, Silvia
ABSTRACT: Objectives: Human milk oligosaccharides (HMOs) are considered to play an important role for the infant. As the biotechnical production of some HMOs is feasible today and clinical studies are being designed, the individual variation of the total amount of HMOs and of single components is of particular importance. Our objectives were to investigate whether differences exist between term and preterm milk, milk from mothers with secretor or nonsecretor status, and a Lewis blood group (a+b−), (a−b+), or (a−b−) pattern. Methods: Within a longitudinal study 96 milk samples (colostrum, transitional, and mature milk) from 32 mothers with preterm (n = 18) and term (n = 14) infants were collected. Delipidated and deproteinized milk was subjected to porous graphitized carbon cartridges followed by high pH anion exchange chromatography with pulsed amperometric detection. Results: Quantitation of 16 single HMOs revealed changes during the first weeks of lactation without discrepancies between term and preterm milk. Significant differences occurred between "secretor" and "nonsecretor" milk (median approximately 10 vs 5 g/L total HMOs). Lacto-N-tetraose (LNT) and lacto-N-fucopentaose (LNFP) II comprised > 55% of the total HMO content in Lewis blood group (a+b−), "nonsecretor" milk and LNT together with 2'fucosyllactose, LNFP I, and difucosyllactose approximately 60% in Lewis (a−b+), "secretor" milk. In Lewis (a−b−), "secretor" milk 80% of oligosaccharides are due to LNT, 2'fucosyllactose, and LNFP I. Conclusions: There are marked differences in total HMOs and single HMOs in milk depending on Lewis blood group and secretor status, which need to be taken into account in clinical studies. Abstract : Supplemental Digital Content is available in the text